Evaluation of Coherence of T wave in Different Leads - Smidtaite, R.; Navickas, Z.; Vainoras, A.; Bikulciene, L.; Poškaitis, V. (Elektronika ir Elektrotechnika, 2009)
Electrocardiogram (ECG) is one of the most general, informative and widely used means for diagnosis of heart diseases. Previous studies have shown that in certain cases concatenation of two processes may reveal much more information than data themselves. This paper introduces several characteristics to evaluate intrapersonal coherence: relations of the same ECG parameter AT1 (amplitude of Twave) in two different leads. Therefore, two time series were cointegrated into one matrix time series. For further investigation matrix analysis was applied. The information revealed by several matrix characteristics was compared visually. Different tendencies of concatenation were noticed, specified by leads and load. Intrapersonal analysis is to be extended to interpersonal in further studies. Ill. 7, bibl. 10 (in English; summaries in English, Russian and Lithuanian).